2015
DOI: 10.1667/rr14036.1
|View full text |Cite
|
Sign up to set email alerts
|

Accelerator-Based Biological Irradiation Facility Simulating Neutron Exposure from an Improvised Nuclear Device

Abstract: We describe here an accelerator-based neutron irradiation facility, intended to expose blood or small animals to neutron fields mimicking those from an improvised nuclear device at relevant distances from the epicenter. Neutrons are generated by a mixed proton/deuteron beam on a thick beryllium target, generating a broad spectrum of neutron energies that match those estimated for the Hiroshima bomb at 1.5 km from ground zero. This spectrum, dominated by neutron energies between 0.2 and 9 MeV, is significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 13 publications
4
59
1
Order By: Relevance
“…Neutron irradiations were performed at RARAF, using an accelerator-based neutron irradiator mimicking the neutron energy spectrum from an IND (22). Briefly, a mixed beam of atomic and molecular ions of hydrogen and deuterium were accelerated to 5 MV potential and used to bombard a thick beryllium target.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Neutron irradiations were performed at RARAF, using an accelerator-based neutron irradiator mimicking the neutron energy spectrum from an IND (22). Briefly, a mixed beam of atomic and molecular ions of hydrogen and deuterium were accelerated to 5 MV potential and used to bombard a thick beryllium target.…”
Section: Methodsmentioning
confidence: 99%
“…To simulate these particular conditions, an accelerator-based neutron irradiation facility was constructed at the Columbia University Radiological Research Accelerator Facility (RARAF; Irvington, NY) (22, 23). The spectrum of neutrons was similar to that encountered in Hiroshima at 1–1.5 km from the epicenter (24), and dosimetry measurements indicated that the neutron exposures contained a ~20% photon dose with neutron energies ranging between 0.2 and 9 MeV, described in detail by Xu, et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this point developments transitioned to optimization of the existing system (7,19) , developing novel bioassays could be performed on the RABiT and testing the existing assays under complex radiation exposure scenarios (20)(21)(22) . The gamma-H2AX and CBMN RABiT assays were transitioned to BARDA funding for further development and rigorous validation in preparation for licensing by the Food and Drug Administration.…”
Section: The Second Funding Cycle (2010-2015)mentioning
confidence: 99%